The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1080/08870440802688588
|View full text |Cite
|
Sign up to set email alerts
|

Living with Type 1 diabetes: A by-person qualitative exploration

Abstract: Type 1 diabetes is a chronic condition which places enormous demands on the individual diabetic. A strict care routine is necessitated, yet even the most controlled and disciplined diabetic is likely to experience associated health problems and automatically faces a reduced life expectancy. The current study explores the psychological repercussions of this situation via a small scale qualitative study which focuses on the very different viewpoints and experiences of four adults living with Type 1 diabetes. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The centrality of personally held goals to the experience of life with diabetes has previously been highlighted by Watts, O'Hara, and Trigg (2010). Their by-case analysis illustrates the potential for psychological conflict, as individuals are forced to contemplate the trade-off between personally held goals and diabetes-related goals.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The centrality of personally held goals to the experience of life with diabetes has previously been highlighted by Watts, O'Hara, and Trigg (2010). Their by-case analysis illustrates the potential for psychological conflict, as individuals are forced to contemplate the trade-off between personally held goals and diabetes-related goals.…”
Section: Discussionmentioning
confidence: 96%
“…We asked how these changes affected their relationship with diabetes. Our use of the term 'relationship' follows Watts, O'Hara and Trigg's (2010) consideration of the 'interaction between person and illness' (p. 493). Each interview concluded with discussion of how satisfied one is with his/her current relationship with diabetes and how he/she views his/her future in light of this relationship.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another meta-analysis found significant Banting, Randle-Phillips positive relationships between T1DM and anxiety symptoms and disorders [14]. A potential cause of mental health difficulties in T1DM is the demanding illness management regime, which can lead to people feeling overwhelmed and hopeless [15,16]. Recent research summarised T1DM as creating a psychological struggle between the successful demands of T1DM management compared to the drive to feel satisfaction of one's own personal goals and ambitions [16].…”
Section: Impact On Mental Healthmentioning
confidence: 99%
“…A potential cause of mental health difficulties in T1DM is the demanding illness management regime, which can lead to people feeling overwhelmed and hopeless [15,16]. Recent research summarised T1DM as creating a psychological struggle between the successful demands of T1DM management compared to the drive to feel satisfaction of one's own personal goals and ambitions [16]. Qualitative research exploring the impact of T1DM in women has found themes of hatred towards their bodies, feeling disadvantaged in not having the same opportunities as those without DM, struggling to feel in control, being vulnerable to the impact of DM, not feeling understood by others, worrying about the impact of DM on their futures and worrying about how others see them [17].…”
Section: Impact On Mental Healthmentioning
confidence: 99%